Echocardiographic reference ranges in older children and adolescents in sub-Saharan Africa. (1st December 2017) - Majonga, Edith D.; Rehman, Andrea M.; McHugh, Grace; Mujuru, Hilda A.; Nathoo, Kusum; Patel, Mohammad S.; Munyati, Shungu; Odland, Jon O.; Kranzer, Katharina; Kaski, Juan P.; Ferrand, Rashida A.
Abstract: Background: Echocardiographic reference ranges are important to identify abnormalities of cardiac dimensions. Reference ranges for children in sub-Saharan Africa have not been established. The aim of this study was to establish echocardiographic z-score references for Black children in sub-Saharan Africa. Methods: 282 healthy subjects aged 6–16 years (143 [51%] males) with no known history of cardiac disease were enrolled in the study in Harare, Zimbabwe between 2014 and 2016. Standard M-mode echocardiography was performed and nine cardiac chamber dimensions were obtained. Two non-linear statistical models (gamma weighted model and cubic polynomial model) were tested on the data and the best fitting model was used to calculate z-scores of these cardiac chamber measures. The reference ranges are presented on scatter plots against BSA. Results: Normative data for the following cardiac measures were obtained and z-scores calculated: right ventricular diameter at end diastole (RVEDD); left ventricular diameter at end diastole (LVEDD) and systole (LVESD); interventricular septal wall thickness at end diastole (IVSd) and systole (IVSs); left ventricular posterior wall thickness at end diastole (LVPWd) and systole (LVPWs); left atrium diameter at end systole (LA) and tricuspid annular plane systolic excursion (TAPSE). Girls had higher values for BMI and heart rate than boys ( p  = 0.048 and p  = 0.001, respectively). Mean interventricular septal and left ventricular posterior walls thickness was higher than published normal values in predominantly Caucasian populations. Conclusion: These are the first echocardiographic reference ranges for children from sub Saharan Africa and will allow accurate assessment of cardiac dimensions in clinical practice.